2017
DOI: 10.1371/journal.pone.0174676
|View full text |Cite
|
Sign up to set email alerts
|

Temporal evolution of vasospasm and clinical outcome after intra-arterial vasodilator therapy in patients with aneurysmal subarachnoid hemorrhage

Abstract: Intra-arterial (IA) vasodilator therapy is one of the recommended treatments to minimize the impact of aneurysmal subarachnoid hemorrhage-induced cerebral vasospasm refractory to standard management. However, its usefulness and efficacy is not well established. We evaluated the effect IA vasodilator therapy on middle cerebral artery blood flow and on discharge outcome. We reviewed records for 115 adults admitted to Neurointensive Care Unit to test whether there was a difference in clinical outcome (discharge m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…In this pilot study of 21 patients with aneurysmal SAH and angiographic vasospasm, we evaluated daily TCD recordings and found that CBFV increased in the days leading up to EVT, which is in accordance with the results of Daftari Besheli et al 43. Moreover, the observation that the MCA and ACA seemed to conform to a similar response, whereas ICA did not change, would further support the proposal that verapamil affects the distal rather than the proximal arteries.…”
Section: Discussionsupporting
confidence: 88%
“…In this pilot study of 21 patients with aneurysmal SAH and angiographic vasospasm, we evaluated daily TCD recordings and found that CBFV increased in the days leading up to EVT, which is in accordance with the results of Daftari Besheli et al 43. Moreover, the observation that the MCA and ACA seemed to conform to a similar response, whereas ICA did not change, would further support the proposal that verapamil affects the distal rather than the proximal arteries.…”
Section: Discussionsupporting
confidence: 88%
“…Interquartile range (IQR) is the difference between the third quartile (Q3: 75%) and the first quartile (Q1: 25%) of a given variable, and therefore, IQR is supposed to be a single number. The authors have given the variable range (Q1-Q3) under IQR, which is not the IQR itself[ 4 , 5 ]. This is an important error from a statistical point of view.…”
Section: To the Editormentioning
confidence: 99%